Methodology for the adjustment of the function of the unbalanced load loss protection - negative ansi 46 sequence of a SIEMENS 7UM62 relay synchronous generator (2019)
(Eng) This paper presents the theory and methodology for the adjustment of the negative sequence current protection function (PF) ANSI 46 of a synchronous generator with poles and poles, for a multifunctional relay SIEMENS 7UM62 that uses for its logic of decision the curve of time of heating allowed of the machine before the in - crease of the magnitude of negative sequence Also the consequences and the damages that can be caused by the excess of current of negative sequence circulating by the stator of the generator are explained. In addition, its functional diagram is illustrated by identifying its input signals: data (settings), analog and bi - nary signals; It also describes in detail its decision process and exit signals. This logical diagram was divided into 3 sub-diagrams to identify the causes that originate their outputs: alarms, startup, firing or blocking, this way of illustrating the process by stages allows greater clarity, since the explanation process is more didactic than the one presented by the manufacturer in the manual. As an example of an illustration, the calculations of the adjustment criteria of the ANSI 46 PF applied to a salient pole generator from Unit 1 of the Salvajina Hydroelectric Plant are presented in detail. This protection function protects the machine by heating load imbalance and asymmetric faults.